2014
DOI: 10.1371/journal.pone.0107352
|View full text |Cite
|
Sign up to set email alerts
|

Is Anyone Listening? Variation in PSA Screening among Providers for Men 75+ before and after United States Preventive Services Task Force Recommendations against It: A Retrospective Cohort Study

Abstract: BackgroundIn 2008, the United States Preventive Services Task Force recommended against prostate specific antigen (PSA) testing for cancer screening in men age 75+.PurposeTo assess PSA screening by primary care physicians (PCPs) before and after recommendations.MethodsIn 2013, this retrospective cohort study analyzed PCPs in Texas with 20+ male patients aged 75+ in both 2007 and 2010, with Parts A and B Medicare. The main outcome was percent of PCP’s male patients 75+ who received PSA testing ordered by the PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Two recent reviews indicated that screening rates have declined, but these reviews synthesized heterogeneous data including self‐reports (which have been shown to be biased), small areas, and different time periods. Two studies that used objective screening measures spanning 2008 to 2012 showed the same pattern as ours, whereas others using shorter time periods or limited areas showed only declining rates . We found no prior studies of change in PSA screening rates in response to guidelines according to race, although two studies found no differential effect of race when examining referral or stage of disease .…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Two recent reviews indicated that screening rates have declined, but these reviews synthesized heterogeneous data including self‐reports (which have been shown to be biased), small areas, and different time periods. Two studies that used objective screening measures spanning 2008 to 2012 showed the same pattern as ours, whereas others using shorter time periods or limited areas showed only declining rates . We found no prior studies of change in PSA screening rates in response to guidelines according to race, although two studies found no differential effect of race when examining referral or stage of disease .…”
Section: Discussionsupporting
confidence: 72%
“…Two studies that used objective screening measures spanning 2008 to 2012 showed the same pattern as ours, 43,44 whereas others using shorter time periods or limited areas showed only declining rates. [45][46][47][48][49][50] We found no prior studies of change in PSA screening rates in response to guidelines according to race, although two studies found no differential effect of race when examining referral or stage of disease. 51,52 Our study has the advantage over these prior studies of using consistent measures of PSA testing well before and after evidence change, with a large enough sample to examine heterogeneity of change across subgroups of men and across areas.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We defined incident cancer as a new diagnosis (none in prior year) of breast or prostate cancer plus evidence of treatment (surgery, radiotherapy, chemotherapy, hormone therapy) as previously defined. 22,23 This excluded 14,715 women with incident breast cancer and 15,245 men with incident prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The United States (U.S.) Preventive Services Task Force [ 1 ], the American Cancer Society [ 2 ], the American College of Physicians [ 3 ], and the American Urological Association [ 4 ] recommend against the use of the prostate-specific antigen (PSA) test to detect prostate cancer in men aged 75 years and older or those with a life expectancy of less than 10 to 15 years, because the risk of harms outweighs potential benefits. Nevertheless, screening rates for PSA tests for prostate cancer detection remain high in clinical practice in older men in the U.S. [ 5 10 ]. The major harm is from over-diagnosis: detecting and treating cancers that otherwise would not have become clinically apparent in the patient’s lifetime [ 5 ].…”
Section: Introductionmentioning
confidence: 99%